Humoral immunity to new coronavirus infection and vitamin D level in healthcare workers - E. A. Krieger; O. V. Samodova; I. V. Schepina; L. L. Shagrov; Yu. M. Zvezdina (Журнал инфектологии, 2023)
Aim: to assess the dynamic changes of humoral immune responses against the S-protein of SARS-CoV-2 and vitamin D level in healthcare workers providing care to COVID-19 patients.Methods. Repeated cross-sectional studies were conducted with an interval of 6 months (May-December 2021) including 170 healthcare workers of infectious settings. An enzyme linked immunosorbent assay was used for the quantitative detection of immunoglobulins G to SARS-CoV-2 and the vitamin D level in the blood serum.Results. In 1.5 years after the start of the pandemic, 91.2% healthcare workers were seropositive to SARS-Co-V-2. In December 2021, this proportion became 98.8%, and the percentage of individuals with high antibodies level (>150 BAU / ml) raised from 49.4% to 77%. Increase in antibodies level induced by vaccination against SARS-CoV-2 was significantly higher in those who have had prior COVID-19 (1031 BAU/мл) compared to those previously vaccinated (367 BAU/ml). The vitamin D level was lower than reference values in 71.2% of health workers and did not correlate with the concentration of antibodies to SARS-Co-V-2.Conclusion. SARS-Co-V-2 seroprevalence among healthcare workers reached almost 100% by the end of the second year of the pandemic. A greater increase in antibodies level after vaccination was observed in healthcare workers previously infected with SARS-Co-V-2 due to formation of hybrid immunity. We did not reveal the association between the vitamin D level and the humoral immune response to SARS-Co-V-2.